RESULTS OF ETIOLOGIC DIAGNOSTICS OF TUBERCULOSIS IN THOSE WITH TB/HIV CO-INFECTION IN THE REPUBLIC OF KARELIA - E. V. Pаkhomovа; Yu. M. Mаrkelov; T. V. Sunchаlinа (Tuberculosis and lung diseases, 2018)
The article presents the analysis of specific clinical and X-ray forms of tuberculosis and results of its etiologic diagnostics in 159 patients with TB/HIV co-infection in the Republic of Karelia from 2001 to 2016. In the Republic of Karelia, it was found out that cavities in lung tissue were less frequent (38.5%) in those with TB/HIV co-infection, however, such patients had infectious forms more often (68.5%) versus pulmonary tuberculosis patients (data from Form no.33). It was defined that improvement of sputum collection would significantly enhance the frequency of tuberculous mycobacteria detection (at least by 20%) in those with pulmonary tuberculosis and HIV infection, which was very important for rapid diagnostics of the disease and prescription of adequate treatment, especially given the fact that nearly ½ (52.8%) of patients suffered from multiple drug resistance.